Peran Bidan dalam Pencegahan Kelainan Genetik Melalui Edukasi dan Konseling Reproduksi - Anjani, Arum Dwi; Aulia, Devy Lestari Nurul; Syaira, Marchellya (Jurnal Ners, 2025)
Factors of infant mortality and morbidity are caused by genetic disorders. Furthermore, cases that occur in Indonesia related to genetic disorders have increased, for example in neural tube defects, Down syndrome, and thalassemia. Based on these incidents, it not only has an impact on the quality of life of children, but also has an impact on the economic, social, and emotional burden on families. The purpose of this writing is to provide analysis results related to the role of midwives in preventing genetic disorders through reproductive education and counseling. The writing refers to qualitative research. Through the results of the analysis carried out, a conclusion is provided related to the role of midwives in preventing genetic disorders through reproductive education and counseling, namely through several strategies including pre-marital and pre-pregnancy education, basic genetic counseling, education about nutrition and the environment, monitoring and education during pregnancy, and community group activities. Through reproductive counseling and education activities related to the prevention of genetic disorders. These reproductive education and counseling activities are preventive and promotive efforts in reproductive health. Based on the education and counseling activities carried out, it is hoped that the community can be more aware of the prevention of genetic diseases and the importance of early detection.